STRUCTURE AND FORMS OF THE ARGUMENT ANALYSIS IN THE MAKING OF THE CITY GOVERNMENT BUDGET POLICY IN MAKASSAR - Saad, Muhammad; Tamma, Sukri (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
This paper aims to analysis the dynamics related to the policy making process related to its structure and forms of argument analysis. Based on the research was conducted in Makassar, within the framework of policy system, this research describes the policy argument structure, analysis of policy analysis forms, reason and ethic in the policy analysis. It is analysis the framework of relationship between policy makers and policy environment in the making of the Local Government Budget (LGB) in the Makassar City Government Fiscal in Year 2016. It is Important to understand how actually the argument and reasons dynamics in develop an important policy. Thru the qualitative method and the argument structure analysis the end of the paper shows the factual process in the policy where seen was an argument competition related to all parties involved related their point of few and interest during the process.